Asesmen Kebutuhan Sarana dan Prasarana Sebagai Dasar Perencanaan Pendidikan dalam Meningkatkan Kualitas Pembelajaran di SMPN 3 Kotabaru - Assyakhirah Nur Ridha; Muhammad Hafiudin Rizaldi; Muhammad Rizhan; Yeslin Anjelina Terayanti; Sulistiyana Sulistiyana (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to describe the needs assessment process of educational facilities and infrastructure as the foundation for educational planning to improve the quality of learning at SMPN 3 Kotabaru. Using a descriptive qualitative approach, data were collected through in-depth interviews, participatory observation, and document analysis. The findings indicate that the needs assessment was conducted using a priority scale approach and reflected in school planning documents (RKS and RAPBS). However, challenges remain in asset documentation and data accuracy, particularly regarding smaller equipment and teacher involvement in formal planning. Despite these limitations, resource constraints have fostered innovation among teachers in utilizing alternative learning media. The implementation of Data-Based Planning (PBD) is considered a strategic solution to enhance the efficiency, accountability, and effectiveness of facilities management. Strengthening data literacy, digitalizing inventory systems, and ensuring synergy between schools and local governments are essential prerequisites for adaptive and sustainable educational planning.